EVALUASI PERFORMA PERTUMBUHAN DAN HETEROSIS PERSILANGAN ANTARA IKAN NILA NIRWANA (OREOCHROMIS NILOTICUS) BETINA DENGAN IKAN NILA BIRU (OREOCHROMIS AUREUS) JANTAN F2 PADA KONDISI TAMBAK HIPERSALINITAS - Adam Robisalmi; Bambang Gunadi; Priadi Setyawan (Research Center for Biology-Indonesian Institute of Sciences, 2020)
Srikandi Tilapia is one of the superior hybridized varieties between black tilapia (Oreochromis niloticus) and blue tilapia (Oreochromis aureus). This fish has fast growth and high salinity tolerance. In its development, efforts are needed to improve and improve its genetic quality. Spawning srikandi tilapia using the parent of male blue tilapia F2 (family selection) is expected to improve performance better than the previous generation.The purpose of this study was to evaluate the growth performance and heterosis value of Srikandi tilapia produced from the extraction of female Nirwana strain tilapia with male blue tilapia F2. Hatchery activities were carried out in freshwater by mass spawning method on the 25 m2 pool. Enlargement activities were carried out at brackish water pond with salinity 25–40 g / L, using net measuring 3×5×1 m3 for 120 days. The stocking density used is 15 fishes / m2. The results of this study indicate that at the final test, the hybridization of Nw ♀x Au (F2)♂ has the best performance with the average of long gain16.60 ± 0.41cm, weight gain 215.33 ± 12.19 g and survival rate 78.50 ± 02.12. Evaluation of heterosis values on the characters of length, weight, survival, and biomass showed a positive value both on the hybridization of Nw ♀x Au (F2)♂ and Au (F2)♀x NW♂. The highest high parent heterosis value for blue tilapia broodstock is shown by population Nw ♀x Au (F2)♂ with values in each character of 6.96% (length), 26.06% (weight), 2.63% (survival), 28.57% (biomass).